O uso do arrendamento do estabelecimento empresarial no soerguimento da empresa em crise e seus limites - Brenner, Matheus Dieterich Espindola (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation aimed to evaluate the capacity of the leasing of the business establishment, as a legal transaction provided for in the Brazilian Civil Code, to shift the economic exploitation of the business activity of a businessperson or business society to another, in order to temporary transfer the business (distinct from the legal entity or its partners) in a situation of crisis. It was also sought to identify and evaluate the hypotheses in which the lessee of the business establishment may be held responsible for the lessor's debts. The study started from the distinction between (i) entrepreneur (business society), as a person of law, (ii) company, as an economic activity, and (iii) establishment, as a complex of goods organized for the exercise of the company, in order to recognize the necessary object of law, capable of satisfying the purpose of shifting business activity from one entrepreneur to another. Next, the study recognized that the Brazilian Civil Code, when defining a specific protection to the business establishment, prescribed the hypothesis that it is the object of constitutive legal transactions, such as the lease of the establishment, through which the temporary constitution of rights of use and enjoyment is sought, with a clear separation between ownership of the establishment and its economic exploitation. With this, the hypotheses of liability of the lessee for the lessor's debts were then analyzed, based on the norms of business law (in particular, articles 1,146 and 1,405 of the Brazilian Civil Code), as well as the norms of tax law, labor law and bankrupt law. Methodologically, the study was developed from practical cases experienced by the author and subsequent bibliographical, doctrinal and jurisprudential research. The author's conclusion was that the establishment's lease agreement is capable of temporarily transferring the business activity from one legal person to another, and this ability allows us to conclude that it is a business capable of being used in the uplift of the company in crisis. As a practical delivery, the author presents a model of a lease instrument for the business establishment.
Keywords: Estabelecimento; Arrendamento; Usufruto; Establishment; Lase; Usufruct; ACCNPQ::Ciências Sociais Aplicadas::Direito